Opportunistic bilateral salpingectomy during gynaecological surgery for benign disease: A survey of current Australian practice. (7th September 2015) - Kapurubandara, Supuni; Qin, Victoria; Gurram, Divya; Anpalagan, Anbu; Merkur, Harry; Hogg, Russell; Brand, Alison
Abstract : Background: Recent evidence supports the fallopian tube as the site of origin for many pelvic serous cancers (PSC) including epithelial ovarian cancers (EOC). As a result, a change in practice with opportunistic bilateral salpingectomy (OBS) at the time of hysterectomy has been advocated as a preventative strategy for PSC in a low‐risk population. Aims: The aim of this study was to assess current clinical practice in Australia with respect to OBS during gynaecological surgery for benign indications. Materials and Methods: An anonymous online survey was sent to all active Royal Australian and New Zealand College of Obstetrics and Gynaecology (RANZCOG) Fellows in Australia. Data regarding clinician demographics and the proportion of clinicians offering OBS were collected. Reasons for and against offering or discussing OBS were sought. A descriptive analysis was performed. Results: The response rate was 26% (280/1490) with 70% of respondents offering or discussing OBS to women undergoing gynaecological surgery for benign indications, usually at the time of abdominal (96%) or laparoscopic (76%) hysterectomy. The main reason for offering or discussing OBS was current evidence to suggest the fallopian tubes as the site of origin for most EOC. Main reasons for not offering OBS were insufficient evidence to benefit the woman (36%) or being unaware of recent evidence (33%). Conclusions: The survey responses indicate that OBS is frequently discussed or offered in Australia, usually at the time of hysterectomy. Given the lack of robust evidence to suggest a benefit at a population‐based level, a national registry is recommended to monitor outcomes.